Kelayakan Media Scrapbook pada Materi Sistem Ekskresi Kelas VIII SMP/MTs - Embun Agresi; Eko Sri Wahyuni; Afandi Afandi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The lack of variety in using learning media makes learning tend to be monotonous and influential on the low of motivation and learning interest of students. The use of digital-based media such as powerpoint, learning videos, and learning websites is not supportive for use because of the limited projector available in schools. With this problem, teachers are more frequent using nondigital-based media such as charta and props until leading to lack of variety in using media. As such, innovation is needed in the use of nondigital-based media such as scrapbook to make the media used is more varied. The aim of this research is to develop and determine the feasibility of the scrapbook on the material of excretion system for eighth grade in junior high school. The method used is research and development. The feasibility test of the scrapbook is carried out by five validators, they are two lecturers of Biology Education in Tanjungpura University and three science teachers in junior high school 1 Selakau, Sambas Regency. The instrument used in data collection is validation sheet. Data analysis using the Aiken (1985) formula. The results of research show that the value in aspect of material, language, graphic components, construction components, and practicality is included in the valid category with a validation average value of all aspects is 0.91. Based on the results of the data analysis from this research, it can be concluded that scrapbook on the material of excretion system for eighth grade in junior high school is worth using as learning media.